Pengembangan Hots Online Assessment Dengan Quizizz Berkarakter Untuk Keterampilan Membaca Pemahaman - Eka Lutfiyatun; Rifda Haniefa (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2022)
Basic Arabic competence for reading comprehension skills at SMA Al Ashriyyah Nurul Iman Parung is included in the Higher Order Thinking Skills (HOTS) category. Therefore, assessment questions should be able to hone logical thinking skills, that is to analyze, evaluate, create, and not just memorize. The degradation of the character of students during the Covid-19 pandemic also requires that online assessments not only focus on cognitive aspects but also pay attention to the characters that appear in the assessment. The purpose of this study was to develop an evaluation tool for Arabic reading comprehension skills based on HOTS using Quizizz, test its feasibility level, analyze students' higher-order thinking skills, and analyze students' responses to the use of Quizizz. This is a Research and Development (R&D) article. Data were obtained through tests, questionnaires, and observations. The research subjects were 32 students of the class XI language program. The product validation result is 88.10 (very feasible). The results of the development show that from the 20 items developed, 19 questions are valid with the calculation of r-count>r-table (0.296). The reliability of the item is 0.986 (very high). The level of difficulty of the questions has an average of "Medium". The results show that students have “Good” higher-order thinking skills in reading comprehension. There 53.8% of students gave a positive response or were satisfied with the use of Quizizz when applying the HOTS online assessment instrument. Hopefully, educators can develop and utilize online assessments with questions that can hone students' reasoning skills in reading comprehension skills and internalizing character values on questions.Keywords - HOTS online assessment, Quizizz, Reading comprehension, Character values.